Evaluation of the contribution of teosinte to the improvement of agronomic, grain quality and yield traits in maize (Zea mays). (15th December 2019) - Wang, Qingjun; Jiang, Yi; Liao, Zhengqiao; Xie, Wubing; Zhang, Xuemei; Lan, Hai; Hu, Erliang; Xu, Jie; Feng, Xuanjun; Wu, Fengkai; Liu, Yaxi; Lu, Yanli
Abstract: Teosinte, an ancestor to modern maize, displays an excellent performance regarding resistance to stress, but its yield potential has rarely been reported. To evaluate the potential contribution of teosinte to maize improvement, two maize–teosinte backcrossed recombination inbred line (RIL) populations and their corresponding test‐cross hybrids were planted for trait assessment. In RN and ZP RIL populations, the average coefficients of variation of 31 agronomic traits were 9.14% (Range, 0.38%‒25.21%) and 6.85% (Range, 0.55%‒27.73%), respectively. The correlation coefficients of 13 common shared traits between RIL populations and test‐cross hybrid populations ranged from 0.10 to 0.60 and from 0.06 to 0.72, respectively. A total of 39 and 3 recombined inbred lines, and 29 and 47 test‐cross hybrids exhibited higher yields than their checks (RP125, Zheng58, CD189 and ZD958) with the BLUP data, respectively. Furthermore, four test‐cross hybrids including RN034/SCML1950, ZP068/Chang7‐2, ZP079/Chang7‐2 and ZP122/Chang7‐2 showed a more stable yield performance, with yield gains of +7.07%, +3.64%, +5.83% and +3.82% over checks, respectively. In conclusion, teosinte could serve as an alien germplasm for maize breeding.